IEEN workshop report: Professionalism in interdisciplinary and empirical bioethics. (December 2014) - Owens, John; Ives, Jonathan; Cribb, Alan
The Interdisciplinary and Empirical Ethics Network was established in 2012 with funding from the Wellcome Trust in order to facilitate critical and constructive discussion around the nature of the disciplinary diversity within bioethics and to consider the ongoing development of bioethics as an evolving field of interdisciplinary study. In April 2013, the Interdisciplinary and Empirical Ethics Network organized a workshop at the Centre for Public Policy Research, King's College London, which discussed the nature and possibility of professionalism within interdisciplinary and empirical bioethics. This paper provides a report of that workshop.